The influence of exposure and physiology on microplastic ingestion by the freshwater fish Rutilus rutilus (roach) in the River Thames, UK - Horton, Alice A.; Jürgens, Monika D.; Lahive, Elma; van Bodegom, Peter M.; Vijver, Martina G. (Environmental pollution (1987), 2018)
Microplastics are widespread throughout aquatic environments. However, there is currently insufficient understanding of the factors influencing ingestion of microplastics by organisms, especially higher predators such as fish. In this study we link ingestion of microplastics by the roach Rutilus rutilus, within the non-tidal part of the River Thames, to exposure and physiological factors. Microplastics were found within the gut contents of roach from six out of seven sampling sites. Of sampled fish, 33% contained at least one microplastic particle. The majority of particles were fibres (75%), with fragments and films also seen (22.7% and 2.3% respectively). Polymers identified were polyethylene, polypropylene and polyester, in addition to a synthetic dye. The maximum number of ingested microplastic particles for individual fish was strongly correlated to exposure (based on distance from the source of the river). Additionally, at a given exposure, the size of fish correlated with the actual quantity of microplastics in the gut. Larger (mainly female) fish were more likely to ingest the maximum possible number of particles than smaller (mainly male) fish. This study is the first to show microplastic ingestion within freshwater fish in the UK and provides valuable new evidence of the factors influencing ingestion that can be used to inform future studies on exposure and hazard of microplastics to fish. [Display omitted] •One third of sampled fish contained microplastics within the gut.•The majority of particles were fibres (75%).•Higher numbers of particles were ingested by individuals with increasing distance downriver.•Larger, female, fish were more likely to ingest the maximum number of microplastics. This is the first study to investigate microplastic abundance within the guts of freshwater fish in the UK, linking ingestion to exposure and physiological factors.